The Role of Oxytocin and the Effect of Stress During Childbirth: Neurobiological Basics and Implications for Mother and Child - Walter, Michael H.; Abele, Harald; Plappert, Claudia F. (Frontiers in Endocrinology, 2021)
The neuropeptide oxytocin acts as a hormone and a neuromodulator, influencing a multitude of human social behaviors, including reproduction. During childbirth and the postpartum period, it plays a key role in regulating and controlling processes that ensure a safe birth and the health of mother and child. Especially the onset of labor, the progress of birth and early breastfeeding are mediated by oxytocin. In the maternal brain it controls the initiation of the mother–infant bond and the mother’s emotional responses towards her child. In this review we summarize the current state of knowledge about the role of oxytocin during the different aspects and mechanisms of human childbirth, combining research from human and animal studies. Physiological and psychological stress during childbirth and lactation can have negative effects on the progress of labor, breastfeeding and bonding. We discuss how maternity caregivers can support the positive effects of oxytocin and minimize the effects of stress. Furthermore, we highlight aspects of the basic neurobiological principles and connections where further research is needed to improve our understanding of the regulation and effects of oxytocin to support maternal and infant health.